Generation Z Students' Perceptions of Asynchronous and Synchronous Learning: A Systematic Literature Review - Machawan, Arsyl Elensyah Rhema; Freda, Azizia (Teaching, Learning, and Development, 2026)
The COVID-19 pandemic has accelerated a major transformation in education, shifting from traditional face-to-face instruction to technology-based online learning. This systematic literature review analyzes Generation Z students' perceptions (born 1997-2012) of asynchronous and synchronous learning in higher education. Following the PRISMA protocol, we identified 487 studies from eight academic databases, with 24 studies meeting our inclusion criteria after systematic screening. Analysis using the Community of Inquiry framework reveals that 92% of studies (n=22) report Gen Z students highly value the flexibility of asynchronous learning. However, 83% of studies (n=20) identify challenges in social presence and self-regulation. Synchronous learning excels in facilitating immediate feedback (reported in 88% of studies, n=21) and social presence (79% of studies, n=19), but faces constraints in flexibility and Zoom fatigue. Uniquely, 75% of studies (n=18) found that Gen Z shows a strong preference for blended approaches featuring micro-learning segments (7-10 minutes), immediate automated feedback, and visually rich content. These findings provide specific practical implications for designing learning experiences responsive to Gen Z characteristics.